IDEOLOGICAL REPRESENTATION OF GLOBALISM IN RADIOHEAD MUSIC VIDEOS (A SEMIOTIC ANALYSIS OF 2+2=5 AND NO SURPRISES MUSIC VIDEOS) - Risca Puspita (Universitas Pendidikan Indonesia (UPI), 2014)
Music video is a media of communication between the musicians and their listener or viewers that conveys message or represents the ideas in a form of images, lyrics and music. This study investigates the way ideological representation of globalism is represented in 2+2=5 and No Surprises music videos. The theoretical framework employs in this research is Barthes’s (1977) semiotic theory of orders signification which focuses on first order signification (denotation) and second order signification (connotation) of the visual elements of music videos. In addition, this study employs Goodwin’s (1992) theory of music video to analyze the key features of music video. The findings of the investigation show that globalism is represented through the lyrics and the visual images in the two music videos. The lyrics analysis shows that the narrative story in 2+2=5 music video signifies public mind control and anger to the totalitarian government. While in No Surprises music video, the narrative story signifies the modern society, an absolute power of the corrupt government, the hopeless and powerless feelings of the lower class society. In the visual analysis, the findings of the investigation show that there are some similarities and differences in the way of illustrating the ideology of globalism in 2+2=5 and No Surprises music videos. The similarities are represented through the use of the symbolic visual style, the use of black and white color saturations and the amplifying relationship between the lyrics and visual. Meanwhile, the differences are represented through the use of warm (red) color saturation that signifies agitation and anger and the intertextual references. Whereas in No Surprises, the use of close up frame size that signifies emotion and the use of cool (blue) color saturation represent the way of illustrating globalism. Keywords: Ideology, Representation, Globalism, Music Video